Microfiltration of saline crude oil emulsions: Effects of dispersant and salinity - Kücük, Şeyma (2022)
Dispersants reduce oil-water interfacial tension making the separation of oil-water emulsions challenging. In this study, crude oil stabilized by the dispersant, Corexit EC9500A, was emulsified in synthetic sea water using a range of Corexit/crude oil concentration ratios (up to 10% by volume). With an interfacial tension of only 8.0 mJ/m2 at 0.5 mL(Corexit)/L, approximately 50% of the crude was dispersed into droplets <10 µm. Near complete rejection of oil in crossflow separation tests was accompanied by a precipitous flux decline attributable in part to dispersant- and salinity-induced decrease in membrane's oleophobicity (4.2 mJ/m2 decrease in surface energy). Screening of electrostatic interactions prompted oil coalescence that occurred at the membrane surface but not in the bulk of the emulsion. Real-time in situ visualization by Direct Observation Through Membrane gave direct evidence of surface coalescence pointing to both its detrimental effects (spread of contiguous films) and possible advantages (removal of large droplets by crossflow shear).